Progress towards a public chemogenomic set for protein kinases and a call for contributions. - David H Drewry; Carrow I Wells; David M Andrews; Richard Angell; Hassan Al-Ali; Alison D Axtman; Stephen J Capuzzi; Jonathan M Elkins; Peter Ettmayer; Mathias Frederiksen; Opher Gileadi; Nathanael Gray; et al. (PLoS ONE)
Protein kinases are highly tractable targets for drug discovery. However, the biological function and therapeutic potential of the majority of the 500+ human protein kinases remains unknown. We have developed physical and virtual collections of small molecule inhibitors, which we call chemogenomic sets, that are designed to inhibit the catalytic function of almost half the human protein kinases. In this manuscript we share our progress towards generation of a comprehensive kinase chemogenomic set (KCGS), release kinome profiling data of a large inhibitor set (Published Kinase Inhibitor Set 2 (PKIS2)), and outline a process through which the community can openly collaborate to create a KCGS that probes the full complement of human protein kinases.